2016
DOI: 10.18632/oncotarget.13215
|View full text |Cite
|
Sign up to set email alerts
|

Gankyrin sustains PI3K/GSK-3β/β-catenin signal activation and promotes colorectal cancer aggressiveness and progression

Abstract: High levels of angiogenesis, metastasis and chemoresistance are major clinical features of colorectal cancer (CRC), a lethal disease with a high incidence worldwide. Aberrant activation of Wnt/β-catenin pathway contributes to CRC progression. However, little is known about regulatory mechanisms of the β-catenin activity in cancer progression. Here we report that Gankyrin was markedly upregulated in primary tumor tissues from CRC patients and was associated with poor survival. Moreover, we demonstrated that ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…Statistical analysis of the numbers of protein nodes revealed that proteins involved in the phosphatidylinositol 3-kinase (PI3K)/AKT signalling pathway (AKT1, TP53, and PI3K family members) were significantly represented in the PPI network core (Figure 4D and 4E ). Constitutive activation of PI3K/AKT signalling promotes the proliferation of various cancers, including pancreatic cancer, while inactivation of this pathway suppresses tumour proliferation, migration, and invasion [ 16 , 17 ]. Reduced PTEN expression indirectly stimulates PI3K-AKT-mTOR activity, thereby contributing to oncogenesis in humans [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Statistical analysis of the numbers of protein nodes revealed that proteins involved in the phosphatidylinositol 3-kinase (PI3K)/AKT signalling pathway (AKT1, TP53, and PI3K family members) were significantly represented in the PPI network core (Figure 4D and 4E ). Constitutive activation of PI3K/AKT signalling promotes the proliferation of various cancers, including pancreatic cancer, while inactivation of this pathway suppresses tumour proliferation, migration, and invasion [ 16 , 17 ]. Reduced PTEN expression indirectly stimulates PI3K-AKT-mTOR activity, thereby contributing to oncogenesis in humans [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the present study demonstrated that inhibition of PSMD10 decreased PTC cell proliferation, migration and invasion. PSMD10 is a regulator of colorectal cancer by phosphoinositide 3-kinase (PI3K)/GSK-3β/β-catenin pathway activation ( 36 ). The present study demonstrated that PSMD10 downregulation repressed GSK-3β/β-catenin and AKT signaling in PTC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of PI3K could be triggered by oncogenes, consequently resulting in the development of tumor (18). Akt is a downstream molecule of PI3K, which is associated with cell growth and EMT, and activated Akt could promote the migration, invasion and EMT of cancer cells such as osteosarcoma cells (19)(20)(21). Therefore, inactivation of PI3K/Akt signaling could be a putative therapeutic strategy for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K can be activated by oncogenes, consequently activated PI3K is capable of promoting the growth and metastasis of tumor cells (18). Akt is a downstream molecule of PI3K, and it is associated with numerous biological processes, such as cell proliferation, invasion and EMT (19). The activation of Akt could induce the migration, invasion and EMT of cancer cells (20).…”
mentioning
confidence: 99%